The clinical value of plasma hepcidin levels in predicting bacterial infections in febrile children - Jia-Huei Yan; Xin-Yuan Cai; Ying-Hsien Huang (Pediatrics and Neonatology)
Background: Febrile children are often evaluated for the risk of bacterial infections in the pediatric emergency department (PER). Hepcidin is an acute phase inflammatory protein. In this study, we examined the plasma hepcidin levels in febrile children. Methods: This study was conducted at a pediatric emergency department with 123 febrile children. We measured plasma hepcidin levels using an enzyme-linked immunosorbent assay. We further evaluated clinical characteristics and routine blood tests along with the hepcidin levels. Results: We observed significantly higher plasma hepcidin levels in bacterial enteritis (p = 0.026) and combined with urinary tract infection (p = 0.007). Furthermore, hepcidin levels had a significantly positive correlation with CRP level and length of hospital stay (R = 0.296, p = 0.001 and R = 0.213, p = 0.018). Hepcidin levels greater than 65 ng/mL also more accurately predicted bacterial infections than values below 65 ng/mL (11.7% vs. 2.1%, Odds ratio 8.4, 95% confident interval 1.7–40.9, p = 0.002). Conclusion: This study provides evidence that febrile children with bacterial infection have higher plasma hepcidin levels, and the values correlated with CRP level and length of hospital stay. Therefore, hepcidin values can potentially be adopted as a biomarker for identifying febrile children with bacterial infection, particularly bacterial enteritis and urinary tract infection. Key Words: bacterial infection, children, CRP, hepcidin